Belmont Castle The Excavation of a Crusader Stronghold in the Kingdom of Jerusalem - Harper, Richard (Council for British Research in the Levant, 2000)
This is the final publication of excavations conducted by the British School of Archaeology in Jerusalem on the Crusader castle of Belmont (Suba) between 1986 and 1989. The account of the excavation is accompanied by specialist reports and concludes with a discussion of the castle's architecture, its military functions, and its economic role. Library of Congress subject headings for this publication: Belmont Castle Site (West Bank) Excavations (Archaeology) -- West Bank. West Bank -- Antiquities. Jerusalem -- History -- Latin Kingdom, 1099-1244.